How safe and effective is oral analgesia for hip fracture patients? – a prospective cohort study - Muhammad, Zehra Abdul; Ahmad, Tashfeen (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the safety and pain reduction profile of routinely prescribed oral analgesics in patients of hip fracture surgery. Method: The single-centre, prospective, cohort study was conducted from June 2022 to July 2023 at the Aga Khan University Hospital, Karachi and comprised adult patients of either gender with hip fractures. The analgesics prescribed at the time of hospital discharge and 1-week follow-up were recorded along with pain and adverse effects till the 2-week post-discharge follow-up. Pain was recorded using the visual analogue scale, with the target score set at 3/10. The relationship between covariates to pain or adverse events was assessed. Possible analgesic-related deaths/adverse events, absolute risk and age-specific death rates were also calculated. Data was analysed using SPSS 19. Results: Of the 133 patients, 80(60.1%) were females and 53(39.8%) were males. The overall median age was 73 years (interquartile range: 16 years). The median pain score was 4 (interquartile range: 2) and 2 (interquartile range: 2) at 1-week and 2-week follow-up, respectively. Adverse events were experienced by 83(62.4%) patients, while 1(0.75%) patient was lost to follow-up at both follow-ups. Of the remaining 132(99.2%) patients, 106(80.3%) were aged >60 years, and 26(19.6%) were aged <60 years. Sub-optimal analgesia at 1-week follow-up with high adverse events was observed after combining acetaminophen with analgesics like ibuprofen (100% and 50% of 2), diclofenac (55% and 50% of 20), meloxicam (50% and 50% of 4), celecoxib (71.4% and 42.8% of 7), tramadol (60% and 57% of 35), pregabalin (100% and 50% of 2), or gabapentin (50% and 50% of 2) respectively. There were 7(5.3%) deaths of which 5(71.4%) were analgesic-related. All 5 of 132 (3.78%) potentially analgesic-related deaths occurred among >60 years of age. Thus, in 106 patients with age >60 years, 5(4.7%) died, and the age-specific death rate was 4,717/100,000 population. The odds of adverse events increased with comorbidity (p=0.02). Pain score was significantly related to adverse events (p=0.007). Conclusion: Combining acetaminophen with other analgesics did not improve analgesia, but did increase adverse events. The risk of adverse events and mortality were higher with comorbidity and older age. Key Words: Adverse drug events, Analgesics, Analgesia, Hip fractures.